La politique étrangère de Donald Trump : une perspective civilisationnelle ? - Jacob Maillet (Revue LISA)
Donald Trump’s foreign policy has often been described as a break with his predecessors’, notably Barack Obama’s. Indeed, diplomacy under the Trump administration seems to be built according to the president’s whims and tweets. Nonetheless, it is sometimes seen as having a “civilisationist” goal, aiming at defending the Judeo-Christian West against the “Muslim threat”. But has such a purpose, assuming it does exist, translated into action? By reviewing the great motions of American foreign policy since the election of the 45th president, this article tries to determine if the Trump administration follows a coherent strategy.